Does previous transurethral prostate surgery affect oncologic and continence outcomes after RARP?. Issue 4 (December 2015) - Su, Yu-Kai; Katz, Benjamin; Sehgal, Shailen; Yu, Sue-Jean; Su, Yu-Chen; Lightfoot, Andrew; Lee, Ziho; Llukani, Elton; Monahan, Kelly; Lee, David
Abstract We examined the effect of previous transurethral resection of the prostate (TURP) on multiple oncologic and continence outcomes after robotic-assisted radical prostatectomy (RARP). We performed a retrospective cohort study of a total of 2693 patients from 2007 to 2014 who underwent RARP. Patients were stratified into 49 patients who had previous TURP prior to RARP (group 1) and 2644 patients who had no TURP prior to RARP (group 2). We collected operative variables including estimated blood loss, operative time, and positive surgical margin (PSM) rates. Urinary continence, defined as 0 pads per day (PPD), and social continence, defined as 1-PPD, were also assessed. American Urological Association Symptoms Score (AUASS), overall ability to function sexually, and Expanded Prostate Cancer Index Composite (EPIC) questionnaire were evaluated at 3 and 12 months after RARP. Weakness of urinary stream (EPIC #4d) at 12 months imposed a greater problem for group 1 patients with prior TURP compared to group 2 patients without prior TURP (p  = 0.012). PSM was not statistically significant between the two groups (p  = 0.110). Group 1 patients had a greater PSM rate (30.61 %) as compared to group 2 (20.95 %). PSM locations in group 1 patients showed the most common locations at the posterior and apex. The difference between the two groups for AUASS, overall sexual function, estimated blood loss, operative time, urinary continence, and social continence was not statistically significant. We examined the effect of previous TURP on postoperative RARP continence and oncologic outcomes. This data can be used to counsel those with prior TURP before RARP.